Professionalisation and Autonomy of the Occupational Therapist Profession in Poland - Cabak Anna; Dąbrowska-Zimakowska Anna; Bartoszewicz Ewelina (Physical Culture and Sport: Studies and Research)
Occupational therapy has been practised for several decades across various medical entities. However, it was only since 2012 that opportunities for professional development in this area began to be created. It can be considered that with the establishment of higher education training in occupational therapy, the perception of this profession has changed and is becoming increasingly important among professionals and the Polish society. Various measures are being taken to regulate the profession (including a law on certain health professions currently under procedure in the Sejm), but the topic of professionalisation and autonomy is still not sufficiently explored and addressed in Polish literature. The aim of this article is to present occupational therapists’ opinions on the professionalisation and autonomy of their profession. A questionnaire was used to survey 188 middle-aged people (35.18±9.72 years). The results show a need to regulate the occupational therapist profession, to guarantee assistance for therapists in improving their qualifications and to increase their remuneration. According to a significant number of respondents, therapists are undervalued and treated unequally in their work environment. The prestige of the occupational therapist profession was rated at a low level. The main conclusion of the study indicates that in the process of professionalisation and autonomy of the profession in Poland, more attention should be paid to the promotion of the contemporary model of occupational therapy in order to increase its recognition and raise awareness of the essence and importance of the role of an occupational therapist in both the medical (therapeutic team) and social environment.